Evaluating the effectiveness of aquatic therapy on mobility, balance, and level of functional independence in stroke rehabilitation: a systematic review and meta-analysis. (January 2020) - Iliescu, Alice Mary; McIntyre, Amanda; Wiener, Joshua; Iruthayarajah, Jerome; Lee, Andrea; Caughlin, Sarah; Teasell, Robert
Objective: To meta-analyze and systematically review the effectiveness of aquatic therapy in improving mobility, balance, and functional independence after stroke. Data Sources: Articles published in Medline, Embase, CINAHL, PsycINFO, and Scopus up to 20 August 2019. Study Selection: Studies met the following inclusion criteria: (1) English, (2) adult stroke population, (3) randomized or non-randomized prospectively controlled trial (RCT or PCT, respectively) study design, (4) the experimental group received >1 session of aquatic therapy, and (5) included a clinical outcome measure of mobility, balance, or functional independence. Data Extraction: Participant characteristics, treatment protocols, between-group outcomes, point measures, and measures of variability were extracted. Methodological quality was assessed using Physiotherapy Evidence Database (PEDro) tool, and pooled mean differences (MD) ± standard error and 95% confidence intervals (CI) were calculated for Functional Reach Test (FRT), Timed Up and Go Test (TUG), gait speed, and Berg Balance Scale (BBS). Data Synthesis: Nineteen studies (17 RCTs and 2 PCTs) with a mean sample size of 36 participants and mean PEDro score of 5.6 (range 4–8) were included. Aquatic therapy demonstrated statistically significant improvements over land therapy on FRT (MD = 3.511 ± 1.597; 95% CI: 0.381–6.642; P = 0.028), TUG (MD = 2.229 ± 0.513; 95% CI: 1.224–3.234; P < 0.001), gait speed (MD = 0.049 ± 0.023; 95% CI: 0.005–0.094; P = 0.030), and BBS (MD = 2.252 ± 0.552; 95% CI: 1.171–3.334; P < 0.001). Conclusions: While the effect of aquatic therapy on mobility and balance is statistically significant compared to land-based therapy, the clinical significance is less clear, highly variable, and outcome measure dependent.